Detecting Dirofilaria immitis: Current Practices and Novel Diagnostic Methods - Damian Pietrzak; Julia Weronika Łuczak; Marcin Wiśniewski (Pathogens)
The nematode Dirofilaria immitis is responsible for a vector-borne disease affecting canines and humans worldwide, known as cardiopulmonary dirofilariasis. An accurate and early diagnosis is of the utmost importance for effective disease management. While traditional microscopy-based methods remain invaluable, they have inherent limitations. Serological tests, in particular ELISA and immunochromatographic tests, are employed due to their capacity to detect D. immitis antigens, offering ease of use and diagnostic accuracy. The advent of molecular methods has the potential to enhance routine diagnostic approaches, with polymerase chain reaction (PCR) and real-time PCR (qPCR) becoming the most prevalent techniques. Despite not yet being integrated into routine diagnostics, which are predominantly based on the Knott’s test and serological methods, these techniques offer significant benefits in the context of scientific research. This article proceeds to examine the potential of advanced techniques, such as high-resolution melting qPCR (HRM-qPCR), loop-mediated isothermal amplification (LAMP), droplet digital PCR (ddPCR), and microRNA (miRNA) detection, which are capable of enhanced sensitivity and early detection. The following work provides an in-depth analysis of the various diagnostic methods, emphasising the necessity of the continuous improvement and adaptation of these tools to effectively combat D. immitis. The findings underscore the importance of integrating these advanced methods into routine practice to improve detection rates and outcomes for infected animals.